Think Like a Hacker, Act Like a Defender: Pelatihan Ethical Hacking bagi Siswa SMA Kristen Karunia Jakarta - Muhammad Adrinta Adurrazzaq; Edwin Lesmana Tjiong; Harya Bima Dirgantara; Atha Fa'iq Abdurrochman; Aqil Ihsaan (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid advancement of digital transformation has increased the complexity of cyber threats, creating a growing need for enhanced digital security literacy, particularly among younger generations. High school students, as digital natives, need to be equipped with cybersecurity knowledge to protect personal data and use technology responsibly. This training program aims to introduce the fundamental concepts of Ethical Hacking as an approach to understanding how cyberattacks operate in order to build stronger defense systems, rather than engaging in illegal hacking activities. The training materials cover the principles of Ethical Hacking, system vulnerability identification, information-gathering techniques, and mitigation strategies against potential cyber threats. Through an educational and practice-based approach, participants are encouraged to develop critical thinking, attention to detail, and ethical awareness in addressing digital security challenges. The expected outcomes include increased cybersecurity awareness, improved ability to identify digital risks, and the development of students who can become responsible, ethical, and security-conscious users and future developers of technology.